Increased replication stress and R-loop accumulation in EGFRvIII-expressing glioblastoma present new therapeutic opportunities. Issue 1 (4th December 2021) - Struve, Nina; Hoffer, Konstantin; Weik, Anna-Sophie; Riepen, Britta; Krug, Leonie; Cetin, Meryem H; Burmester, Jasmin; Ott, Leonie; Liebing, Jana; Gatzemeier, Fruzsina; Müller-Goebel, Justus; Gerbach, Mirja; et al.
Abstract: Background: The oncogene epidermal growth factor receptor variant III (EGFRvIII) is expressed in approximately one-third of all glioblastomas (GBMs). So far it is not clear if EGFRvIII expression induces replication stress in GBM cells, which might serve as a therapeutical target. Methods: Isogenetic EGFRvIII− and EGFRvIII+ cell lines with endogenous EGFRvIII expression were used. Markers of oncogenic and replication stress such as γH2AX, RPA, 53BP1, ATR, and CHK1 were analyzed using western blot, immunofluorescence, and flow cytometry. The DNA fiber assay was performed to analyze replication, transcription was measured by incorporation of EU, and genomic instability was investigated by micronuclei and CGH-Array analysis. Immunohistochemistry staining was used to detect replication stress markers and R-loops in human GBM samples. Results: EGFRvIII+ cells exhibit an activated replication stress response, increased spontaneous DNA damage, elevated levels of single-stranded DNA, and reduced DNA replication velocity, which are all indicative characteristics of replication stress. Furthermore, we show here that EGFRvIII expression is linked to increased genomic instability. EGFRvIII-expressing cells display elevated RNA synthesis and R-loop formation, which could also be confirmed in EGFRvIII-positive GBM patient samples. Targeting replication stress by irinotecan resulted in increased sensitivity of EGFRvIII+ cells. Conclusion: This study demonstrates that EGFRvIII expression is associated with increased replication stress, R-loop accumulation, and genomic instability. This might contribute to intratumoral heterogeneity but may also be exploited for individualized therapy approaches.